EFFECT OF TEMPERATURE ON DEVELOPMENT AND MORTALITY OF IMMATURE STATES OF Callosobruchus maculatus F. (Coleoptera: Bruchidae) IN GARBANZO - ALDANA-ALFONSO, HÉCTOR MIGUEL (Revista Colombiana de Entomología, 1983)
The temperature effect on the development and mortality on the immature stages of Callosobruchus maculatus F. was investigated, to establish the minimum temperature of development as well as the most sensible stage to the temperature. Using one egg per chickpea seed, six groups with 30 individuals for each temperature used (20 and 25°C) were formed. The relative humidity was 75± 5%  and both experiments were carried out under dark conditions. The duration for each one of the inmature stages was determined as well as the total duration of development, from egg to adult stage. By using the formula y (t-a) = Kit was possible to calculate the minimum temperature of development for the species. The results showed that the minimum temperature of development was 12,96°C. Furthermore, the thermal constant was 517,09 degrees-days. There is an inverse relationship between the rearing temperature of the insect and its development duration, which was of 73,46 days at 20°C and 42,94 days at 25°C. Moreover, it was possible to prove that the larval stage is the most sensible to the temperature since the mortality was 49,11% and 25,49°/o at 20 and 25°C respectively.